TI_GERICHTE 12.2004.87 vom 5. Juli 2005 , architetto - revoca del mandato - onorario - calcolo - nuovi fatti - irricevibilità - TI Tribunale d'appello (2005)
architetto - revoca del mandato - onorario - calcolo - nuovi fatti - irricevibilità